Baseline Inspection and Measurement of Local Exhaust Ventilation (LEV) Systems at Spray Booth in Manufacturing Plant - Said, Md Radzai; Hasan, Nor Halim; Leman, A.M.; Abd Rahman, Majahar (Selcuk University, 2013)
Examination and testing of local exhaust ventilation systems (LEV) that was conducted could help the management to create base or annual performance measurement in industry operations.The LEV will also be verified compliance with original design data, in order to determine adequate of transport velocities are being maintained. The examination also to determine if additional exhaust hoods can be added to the existing systems and compliance with Occupational Safety and Health (OSH) regulations.This Examination is to obtain the necessary data such as airflow static pressure, speed and total pressure at appropriate points LEV system. The method used is to inspect, analyze and evaluate the performance of local exhaust ventilation systems and related components, evaluate and recommend necessary measures for the restoration or repair of the damage.LEV also need to carry out inspection and tested by a registered professional engineer after construction and installation to demonstrate that the equipment meets the design specifications.Methodology for measurement and testing were based on American Conference of Governmental Industrial Hygienist (ACGIH). Selections of testing points for fume hood and canopy hood with individual suction fan, face velocities were measured and where applicable and accessible, duct transport velocities and static pressure measurements were carried out. Results from measurement data obtained is 65 fpm face velocity and flow rate 6500 fpm is lower than the value proposed by the ACGIH and show spray booth is not able to bring out the contaminants out of the workplace. The LEV systems has been examined and tested; both spray booth number1 and number 2 was below the ACGIH Standard while measurement and inspections conducted and not comply with local legislation to protect workers safety and health.